Fundamental Beta pada Perusahaan Properti yang terdatar di Bursa Efek Indonesia Periode 2018-2022 - Tegar Maulana Hidayat; Adler Haymans Manurung; Jhonni Sinaga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of Return on Equity, Fixed Asset, Price Book Value, Asset Growth, and Effective Tax Rate on Stock Beta. The data collection method used is using data from the financial statements of property companies. This study was analyzed using descriptive analysis, classical assumption analysis, multiple regression analysis, coefficient of determination, and t-test. The results of this study indicate that the effect of ROE has a positive and insignificant effect on stock beta, fixed assets have a positive and insignificant effect on stock beta, price book value has a negative and significant effect on stock beta, asset growth has a positive and significant effect on stock beta, and effective tax rate has a positive and insignificant effect on stock beta.